MathOverflow is a question and answer site for professional mathematicians. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given a curve $f(x)$ (for $x \in [0,1]$), and a line $y=a$, let $U$ be the total area below $f$ and above $a$, and let $L$ be the total area above $f$ and below $a$. If $L=U$, this means that $a =\int_0^1 f(x) dx$.

Or if $f(x)$ is a sequence of $n$ numbers, this means $a$ is their mean. Equivalently, $U = \int_0^1 \max(f(x)-a,0) \; dx$, $L = \int_0^1 \max(a-f(x),0) \; dx$.

What I want instead is the value $a$ for which $c \cdot L = U$, for some constant $c>0$.

This can be computed approximately by binary search or exactly with a more cumbersome algorithm, but: is there a closed-form expression for this value? And: has this value been studied?

share|cite|improve this question
Why do you ask? Does this question come from somewhere? – Igor Rivin Aug 9 '11 at 15:55
From a battery-charging problem, where $a$ is the constant level of energy available, and $f$ is the energy usage at each moment. So $L$ corresponds to charging into the battery, and $U$ corresponds to discharging from the battery. Because of charge/discharge inefficiencies, after charging 1 unit in, you'll only be able to discharge, say, .5 units out. (For this interpretation to make sense, you might assume $f$ is monotonically increasing.) – matt j Aug 9 '11 at 19:20
You can't provide any further information about $f$? That would help greatly for a "closed form"... – J. M. Aug 14 '11 at 17:48
@J.M.: $f$ can just be a step function of with $n$ unit-width steps. – matt j Aug 15 '11 at 9:50

I can't give you a closed form, but maybe rewrite it in a more useful form.

First denote by $A$ the total area $A=\int_0^1 f(x)\;\mathrm{d}x$. Note that $U-L=A-a$.

Then your question is equivalent to solve $(c-1)L=A-a$ for $a$. In the case where $f$ is strictly monotone with inverse $f^{-1}$ and normalized such that $f(0)=0$, we have that $$ L = a f^{-1}(a) - F(f^{-1}(a)) , $$ where $F$ is the antiderivatve of $f$. Setting $a=f(y)$ we obtain that $$ L(y) = yf(y) - F(y). $$ Note that $$ L'(y) = y f'(y) >0 \qquad\text{for } y\in (0,1) . $$ And hence we have to solve the following equation for $y$ $$ A = (c-1)L(y) + f(y) = (c-1)\int_0^y x f'(x)\;\mathrm{d}{x} + f(y) = \int_0^y [(c-1)x+1]f'(x)\;\mathrm{d}{x}$$ and set afterwards $a=f(y)$. In the case $c=1$, this simplifies to the known formula $f(y)=A$ and hence $a=\int_0^1 f(x)\;\mathrm{d}{x}$.

share|cite|improve this answer
Why should it be that $L+U = \int_0^1 f(x) dx$? If $f(x)=10$ and $c=1$, for example, then $L=U=0$ but $\int_0^1 f(x) dx=10$. – matt j Aug 15 '11 at 9:49
I'm sorry. I misread your question. My post answers not your question. – André Schlichting Aug 15 '11 at 11:37
I have rewritten my answer in the context of the question. It is maybe not really helpful, but at least should be more correct now. – André Schlichting Aug 15 '11 at 12:10

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.